Market Structure and Extortion: Evidence from 50,000 Extortion Payments - Brown, Zach Y; Montero, Eduardo; Schmidt-Padilla, Carlos; Sviatschi, Maria Micaela (Review of Economic Studies, 2025)
Abstract How does gang competition affect extortion? Using detailed data on individual extortion payments to gangs and sales from a leading wholesale distributor of consumer goods and pharmaceuticals in El Salvador, we document evidence on the determinants of extortion payments and the effects of extortion on firms and consumers. We exploit a 2016 non-aggression pact between gangs to examine how collusion affects extortion in areas where gangs previously competed. While the pact led to a large reduction in competition and violence, we find that it increased the amount paid in extortion by approximately 20%. Much of this increase was passed through to retailers and consumers: retailers experienced an increase in delivery fees, leading to an increase in consumer prices. In particular, we find an increase in prices for pharmaceutical drugs and a corresponding increase in hospital visits for chronic illnesses. The results point to an unintended consequence of policies that reduce competition between criminal organisations.